Hubungan Antara Dukungan Sosial dengan Tingkat Kecemasan pada Korban Perundungan - Azizah Rofifatun Nauroh Gunadi; Wahyu Endang Setyowati; Betie Febriana (CV SCRIPTA INTELEKTUAL MANDIRI, 2025)
Bullying is a form of psychosocial violence that frequently occurs among adolescents and can lead to long-term negative impacts on mental health, including anxiety. In such conditions, social support from family, peers, and the surrounding environment plays an important protective role in helping adolescents reduce anxiety levels and accelerate psychological recovery. To determine the relationship between social support and anxiety levels among bullying victims. This study employed a quantitative design with a cross-sectional approach. The study population consisted of 63 bullying victims, all of whom were selected using a total sampling technique. Research instruments included the Multidimensional Scale of Perceived Social Support (MSPSS) and the Zung Self-Rating Anxiety Scale (ZSAS). Data analysis was conducted using the Spearman Rank test. Most respondents were aged 16–25 years and were predominantly university students. Based on variable distribution, the majority of respondents reported low social support and moderate levels of anxiety. Bivariate analysis indicated a significant relationship between social support and anxiety levels with p = 0.00 (p < 0.05), meaning that higher social support is associated with lower anxiety. There is a strong and significant negative relationship between social support and anxiety levels among bullying victims at UPTD PPA Kota Bogor.